GOOD GOVERNANCE AND ACCOUNTABILITY IN A DEMOCRACY - Gyong, John Emmanuel (European Scientific Journal, ESJ, 2014)
In spite of the fact that Nigeria is one of the highest producers of petroleum products in the world, the country has remained backward in socio-economic and political development. Consequently, malnutrition, poor health prospects, unemployment, abject poverty, rising insecurity and political instability have been the hallmark of the nation. One of the major factors that accounts for the failure of most African countries, including Nigeria, to attain development has been the absence of good governance and accountability in their democratic experiments. The reasoning is that without good governance being institutionalized through accountability, democratic consolidation would be jeopardized. The paper observes that democratic development in Nigeria has gone through cheaquered history. It therefore argues that that good governance as reflected in the areas of social, political and economic advancement is a necessary prerequisite to the attainment of a full fledge democracy. However, the paper identifies a number of challenges to the attainment of good governance and accountability in Nigeria. The paper then further argued that there are still prospects towards the attainment of good governance and accountability. In conclusion, the paper posits that in order to promote good governance and accountability in Nigeria, there is the need to entrench the principles of majority rule, healthy intra and inter party competition, free and fair election, separation of power between the Executive, Legislature and the Judiciary, strict adherence to due process of law, effective participation of civil society groups, the media as well as civil right for all and sundry.